Pengaruh Social Media Marketing terhadap Brand Loyalty dengan Value Consciousness dan Brand Consciousness Sebagai Variabel Mediasi: Studi Kasus Pelanggan Kopi Janji Jiwa - Adhitya Nugraha; Soepatini (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the impact of Social Media Marketing on Brand Loyalty, with Value Consciousness and Brand Consciousness as mediating variables. A case study was conducted on Kopi Janji Jiwa customers, focusing on how social media marketing influences brand loyalty and the effects of value awareness and brand awareness as mediators in this process. The research method involved data collection through surveys of respondents who are loyal customers of Kopi Janji Jiwa. The results of data analysis indicate that Social Media Marketing has a positive and significant influence on Brand Loyalty. Furthermore, Value Consciousness and Brand Consciousness are proven to mediate the relationship between Social Media Marketing and Brand Loyalty. This means that social media marketing not only strengthens brand loyalty directly but also through the influence generated on the value awareness and brand consciousness of customers.